Measuring the Impact of Apply Reverse Engineering Approach to Production Cost Reduction on The Economic Growth - Al Uwaimri, Ahmed (International Journal of Economics Development Research (IJEDR), 2025)
The quantitative results from the application of the reverse engineering approach showed a reduction in extraction costs by $1.8, compared to the target reduction of $3.8. Meanwhile, the total cost per oil barrel increased to $27, exceeding the target cost of $25.2 per barrel. Oil production in the Sultanate of Oman increased by 3.6%, reaching 3,323,800 barrels by the end of January 2023. The average oil price in 2022 was $94 per barrel. Based on these figures, the profit margin after achieving the target cost reduction is $94 – $25.2 = $68.8, resulting in a total profit of 3,323,800 × $68.8 = $228,677,440. The reverse engineering approach in reducing production costs helps increase profit margins and supports oil-based economies in generating higher revenues, thereby contributing to the promotion of economic growth in oil-exporting countries. As an innovative tool, the application of reverse engineering in production cost reduction demonstrates a significant impact on promoting economic growth in oil-exporting economies.